Toward a Political Economy of Takings - Jeffry A. Frieden (Washington University Journal of Law & Policy, 2000)
In this Essay, I offer the musings of one whose own work is of political economy and an area of political economy far removed from the issues typically raised by takings.
Keywords: Land use; Regulatory taking (Law)